Androgini: Popularitas dan Eksistensi Bagi Remaja di Era Digital - Asima Sitanggang (Jurnal Spektrum Komunikasi, 2020)
This research raises the issue of androgyny which is one of the classifications of individuals across gender roles: masculine, feminine, androgynous, and undifferentiated-different from lesbian, gay, bisexual, and transgender (LGBT). The purpose of this study is to analyze androgynous self-disclosure on social media where self-identity is not only limited to how a person expresses himself but shifts to an effort to compare oneself, to one’s attraction or selling power and as a way to exist. The author uses a qualitative approach with a multiliterate review from books, journals, symbols, and armed with critical and collaborative thinking. The author concludes that fashion becomes the language of androgynous communication and self-expression of an unusual figure is strong personal branding. It becomes an influence for those who follow them where the influence is the political power to accept the existence of androgyny, change the thoughts, and influence others especially the youth in the digital era.